PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN DI WISMA RAMAYANA TANJUNGBATU KUNDUR - Diani, Diani; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2022)
The hotel industry plays an important role as one of the supporting sectors for tourism. The hotel business is growing rapidly due to the increasing demand for such services as well as the growing opportunities for travel. In order to maintain the position held and to compete in the future, it is necessary to provide services and facilities by which old customers can be retained, and new customers can be attracted. This study aims to determine the effect of service quality and facilities on satisfaction at Wisma Ramayana Tanjungbatu Kundur. In this research method is quantitative causality research. Data collection techniques were carried out by distributing questionnaires to 132 respondents. The data analysis technique uses the analysis of validity, reliability, normality, multicollinearity, heteroscedasticity, linear regression analysis, t test and F test with the SPSS (Statistical Product and Service Solution) version 22. The results showed that the quality of service, facilities had a significant partial and simultaneous significant effect on customer satisfaction.. The results of the R Square value test show that the quality of service and facilities is 83.1%, while the remaining 16.9% is influenced by other variables not examined in this study. The results of the T test show that the value of the service quality of the t-count variable is 15.115 and the facility is 6.119, the value of these two variables is greater than the t-table so it can be concluded that the quality of service and facilities has a positive and significant effect on customer satisfaction.